Water Scavenger Beetles (Coleoptera: Hydrophilidae) from Bingo! Province of Turkey - Mart, Abdullah; Erman, Orhan (Zoological Soc Pakistan, 2017)
Twenty nine species and 2 subspecies belonging to 10 genera of water scavenger beetles (Coleoptera Hydrophilidae) collected from Bingol province between May 2003-October 2004 have been described.